Activities to Improve the Intercultural Communicative Competence in the Training of Translators at Universidad Central “Marta Abreu” de Las Villas - Domínguez Monzón, Sahily; Morales Triana, Marilín; Rodríguez Ruiz, Mayra; Barea Martínez, Lidaisy (Feijóo, 2021)
Intercultural communicative competence (ICC) is an essential tool in the English Language teaching and learning process, especially in the training of translators. In the current globalized world, the translator needs to acquire a certain level of intercultural communicative competence (ICC) in order to function as a bridge between different sociocultural groups, minimizing the effects of cultural misunderstandings. Therefore, the main goal of this research paper is to propose a set of activities for the subject Introducción a la Traducción in the third academic year of the course English Language with Second Foreign Language (French) at Universidad Central “Marta Abreu” de Las Villas (UCLV) for students to become interculturally competent translators. The paper consists of two chapters. Chapter 1 focuses on the theoretical framework about culture, interculturality, communication, language, intercultural communication and intercultural communicative competence, as well as the relationships between them. Chapter 2 deals with the methodological framework, stages and context of the research. Also, the activities proposed are described in this second chapter. Finally, conclusions, recommendations, bibliography and annexes are provided.
Keywords: Culture; Intercultural Communicative Competence; Interculturality; Language; Translator Training; Lengua Inglesa